Functional status of community-dwelling older adults after inpatient rehabilitation. (2nd January 2022) - Peiris, Casey L; Shields, Nora; Lowe, Anna; Tan, Germaine; Taylor, Nicholas F
Abstract : Background/aims: Factors that influence functional ability in older adults after rehabilitation are not well understood. The aim of this study was to investigate how older people function in their community after being discharged from inpatient rehabilitation. Methods: A cross-sectional study was undertaken of community-dwelling older adults ( n =86, 75 ± 6 years) discharged from rehabilitation in the previous 12 months. Basic functional independence was assessed using the Functional Independence Measure and complex functional independence was assessed using the Frenchay Activities Index. Multiple regression analyses were conducted to assess any association between predetermined factors and function. Results: Functional Independence Measure scores and physical activity levels after being discharged accounted for 50% of the variance in basic function ( R 2 =0.50, F =40.75, P <0.001). Frenchay Activities Index scores, physical activity, age, sex and migrant status accounted for 68% of variance in complex function (R 2 =0.68, F =29.75, P <0.001). Conclusions: Clinicians are encouraged to implement strategies to improve function at discharge from rehabilitation and to promote physical activity among older people at risk of poor function following rehabilitation.